2010
DOI: 10.1007/s00520-010-0972-0
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of the cancer anorexia–cachexia syndrome

Abstract: Cancer-anorexia cachexia animal models are numerous. No one is ideal. The choice should depend on the research question. To investigate cancer-anorexia cachexia independent of pro-inflammatory cytokine effects, the MAC16 ADK and XK1 are useful. MAC16 ADK helps study the host's tumor metabolic effects, independent of any anorexia or inflammation. XK1 is both anorectic and cachectic, but data about it is limited. All other models induce a host inflammatory response. The Walker 256 ADK and MCG 101 are best avoide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 69 publications
(65 reference statements)
1
61
0
Order By: Relevance
“…LPS administration induced anorexia, which is in line with previous studies (Gautron et al 2005, Ogimoto et al 2006. LPS administration stimulates the release of pro-inflammatory cytokines such as IL1, TNFa, IL6, and so on (O'Reilly et al 1988, Plata-Salaman 1999, Wong & Pinkney 2004, Bennani-Baiti & Walsh 2011. These cytokines may be associated with the induction of anorexia; however, hypothalamic inflammatory signals, rather than peripheral, have been identified as the major causes of LPS-induced anorexia (Laye et al 2000, Plata-Salaman 2000, Wisse et al 2007).…”
Section: Nfkb Activation In the Hypothalamus Is Involved In Lps-inducsupporting
confidence: 87%
“…LPS administration induced anorexia, which is in line with previous studies (Gautron et al 2005, Ogimoto et al 2006. LPS administration stimulates the release of pro-inflammatory cytokines such as IL1, TNFa, IL6, and so on (O'Reilly et al 1988, Plata-Salaman 1999, Wong & Pinkney 2004, Bennani-Baiti & Walsh 2011. These cytokines may be associated with the induction of anorexia; however, hypothalamic inflammatory signals, rather than peripheral, have been identified as the major causes of LPS-induced anorexia (Laye et al 2000, Plata-Salaman 2000, Wisse et al 2007).…”
Section: Nfkb Activation In the Hypothalamus Is Involved In Lps-inducsupporting
confidence: 87%
“…Control rats received saline injections on the same day of tumour inoculation. Cachectic syndrome is observed in rats bearing Walker 256 tumour cells after 10-15 days (Bennani-Baiti & Walsh 2011). To evaluate the development of cancer cachexia, the experiments were carried out in the time course study, when the rats were killed on days 4, 7, 10 or 14 post-injection (seven to ten animals on each time point) by decapitation after 12 h fasting.…”
Section: Animalsmentioning
confidence: 99%
“…However, there are many limitations when extrapolating such models to the human situation, including the more acute versus chronic timescales of tumor growth and development of muscle wasting (8). Because of the invasive nature of clinical protocols to date, there are few studies of skeletal muscle protein metabolism in human cancer cachexia and these have demonstrated either markedly reduced (9) or unchanged (2) fractional synthetic rate (FSR) when compared with controls.…”
Section: Introductionmentioning
confidence: 99%